The prince: jonathan eaudiobook Sons of encouragement series, book 3. - Rivers, Francine (Sons of Encouragement, 2017)
His zeal carried him into battle. His faithfulness won him honor among his people. His humility led him into friendship with the man who would become king in his place. David was a man after God's own heart. But it was the courage and selflessness of his best friend that opened the door to David's rule. A man of honor and deep faith. Jonathan